Ukraine Gas Pricing Policy : Distributional Consequences of Tariff Increases - Mitra, Pritha (IMF Working Papers; Working Paper ;, 2012)
Ukraine's gas pricing policy subsidizes gas and heating for all households. As the cost of imported gas rises, this policy increasingly weighs on government finances, sustains energy over-consumption, dampens investment in delivery systems, and undermines incentives for domestic production. However, gas price hikes have been deferred to the medium-term as they are politically unpopular. Through estimation of household demand functions by income quintiles to evaluate the distributional consequences of tarrif reform, this paper finds that tariff reforms combined with targeted social support can address the economic inefficiencies of the current pricing policy without large welfare costs to the lower income segments of the population.